The effect of load models on unstable low-frequency oscillation damping in Taipower system experience w - Wen-Shiow Kao
This paper uses the eigenvalue analysis approach to observe the impact of load models on an unstable low frequency oscillation damping, which recently occurred in the Taiwan power system. In order to enhance oscillation damping, the effect of load models on power system stabilizers is also investigated. Three kinds of the derived load models (a dynamic model, a composite model, and an exponential model) based on the component approach with the measured characteristics of power system loads are used in this paper. Time simulation results are extensively used to verify the eigenvalue analysis results with and without power system stabilizers. One set of field test data obtained from the Taiwan power nuclear plant with power system stabilizers is used to determine which load model provides a more accurate result in enhancement of oscillation damping. Depending on the results, the effect of load models on electromechanical oscillation damping with and without power system stabilizers is verified
Keywords: Taipower; Taiwan power system; Composite model; Control simulation; Dynamic model; Eigenvalue analysis approach; Electromechanical oscillation damping; Exponential model; Load models effect; Nuclear power plant; Power system stabilizers; Time simulation; Unstable low-frequency oscillation damping